Mechanisms of human neutrophil elastase-catalysed inactivation of factor VIII(a) - Nogami, Keiji; Ogiwara, Kenichi; Matsumoto, Tomoko; Nishiya, Katsumi; Takeyama, Masahiro; Shima, Midori (Thrombosis and Haemostasis, 2011)
Mechanisms of inflammation and coagulation are linked through various pathways. Human neutrophil elastase (HNE), can bind to activated platelets, might be localised on platelet membranes that provide negatively-charged phospholipid essential for the optimum function of tenase complex. In this study, we examined the effect of HNE on factor (F)VIII. FVIII activity was rapidly diminished in the presence of HNE and was undetectable within 10 minutes. The inactivation rate waŝ8-fold greater than that of activated protein C (APC). This time-dependent inactivation was moderately affected by von Willebrand factor. HNE proteolysed the heavy chain (HCh) of FVIII into two terminal products, A11–358 and A2375–708, by limited proteolysis at Val358, Val374, and Val708. Cleavage at Val708 was much slower than that at Val358 in the >90-kDa A1-A2-B compared to the 90-kDa A1-A2. The 80-kDa light chain (LCh) was proteolysed to 75-kDa product by cleavage at Val1670. HNE-cata- lysed FVIIIa inactivation was markedly slower than that of native FVIII (by ~25-fold), due to delayed cleavage at Val708 in FVIIIa. The inactivation rate mediated by HNE was ~8-fold lower than that by APC. Cleavages at Val358 and Val708 were regulated by the presence of LCh and HCh, respectively. In conclusion, HNE-catalysed FVIII inactivation was associated with the limited-proteolysis that led to A11–358, A2375–708, and A3-C1-C21671–2332, and subsequently to critical cleavage at Val708. HNE-related FVIII(a) reaction might play a role in inactivation of HNE-induced coagulation process, and appeared to depend on the amounts of inactivated FVIII and active FVIIIa which is predominantly resistant to HNE inactivation.Note: An account of this work was presented at the 51st annual meeting of the American Society of Hematology, December 10, 2009, New Orleans, LA, USA.
Keywords: FVIII; FVIIIa; human neutrophil elastase (HNE); inactivation; proteolysis